Sweet's syndrome and a Mirena® intrauterine system. Issue 2 (1st April 2004) - Hamill, Matthew; Bowling, Jonathan; Vega-Lopez, F
Abstract : A woman fitted with a Mirena® intrauterine system (IUS) for menorrhagia presented with a short history of fever and progressive skin lesions. Histological examination of a skin biopsy was compatible with the clinical diagnosis of Sweet's syndrome. Treatment was with topical and oral steroids, however the condition relapsed on reduction of the steroid dose. Symptoms finally resolved on removal of the IUS and the patient remained symptom free at 9-month follow-up. There have been previous reports of Sweet's syndrome in association with hormonal contraceptives, however this is believed to be the first reported case in association with a Mirena IUS.